ENHANCING THE STUDENTS' SCIENTIFIC LITERACY WITH ETHNOSCIENCE APPROACH IN SURABI CONTEXT FOR LEARNING FOOD ADDITIVES - Nadira Renata Putri, - (2021)
Science literacy has become an important skill in the digital era because someone with science literacy skills will connect science principles to technology, global development, and society. Since Indonesia has low rank in PISA, this research aims to analyze ethnoscience approach to enhance students' scientific literacy. Pre-experimental with one group pre-test and post-test was used as a research method and design. There are 34 students in grade 8th from one of the private schools in Bandung who were chosen by convenience sampling. The improvement in students' scientific literacy is measured by conducting objective tests and doing learning observation. The result showed a significant improvement in students' scientific literacy, especially in the competence and attitude domain. It can be seen from the improvement of pre and post-test score. In addition, students tend to explain rather than evaluate the scientific principle. On the other hand, most of the students already have a good attitude which didn't affected by the learning process. The implementation of ethnoscience approach in class makes student share the relation between their experience and science. For better results, all domains in scientific literacy have to be analysis the deeper explanation. Also, the context in culture have to be consider and prepare well.